Salud mental y adicciones en un adolescente de 17 años de la ciudad de Quevedo - Calvache Bravo, Luis Adrian (2023)
The objective of this research work is the mental health problem that affects addictions in a 17-year-old adolescent, which was carried out in the city of Quevedo, because he has cognitive and intellectual impairments that are affecting his interpersonal development. and school. The present research is carried out using mixed methodology, since techniques were used that allowed obtaining both quantitative and qualitative data, these methods used are clinical and psychometric methods, the following techniques were also used: semi-structured interview, clinical history, clinical observation, ASSIST V3.0 scale, Beck Depression Inventory and H.T.P. The results of this case study indicate that the patient meets the diagnostic parameters according to the DSM-5, which is a depressive disorder. The patient's symptoms entail a period of increase of three months, that is, the health problems Mental disorders affect addictions in 17-year-old youth; these same problems trigger symptoms in the patient that affect their quality of life at an interpersonal level and in important areas of their life.